Hubungan antara Kepatuhan Penggunaan APD (Alat Pelindung Diri) dengan Dampak Paparan sianida di Area HLO (Heap Leach Operation) PT. Bumi Suksesindo - Diana Anwar; Abdul Rohim Tualeka; Syifa'ul Lailiyah (Universitas Airlangga, 2024)
Background: The mining sector plays a crucial role as a significant contributor to the energy supply, which is vital for economic growth. However, mining activities pose various potential hazards. Unfortunately, compliance with the usage of Personal Protective Equipment (PPE) in this industry remains relatively low. Objectives: The objective of this research is to analyze the relationship between workers' compliance in using PPE and the potential impact of cyanide exposure in the Heap Leach Operation (HLO) irrigation area of PT. Bumi Suksesindo. Methods: This study employed a quantitative research approach using an observational analytical method and a cross-sectional design. The research population consisted of 33 workers in the irrigation section of the HLO area. Data collection is conducted through questionnaire surveys, and the obtained data are analyzed using the contingency coefficient (c) to determine the strength of the relationship between variables. Results: The majority of workers (60.6%) were not exposed to the impact of cyanide exposure. There is a very weak correlation between compliance in using PPE and the potential impact of cyanide exposure (c = 0.141) Conclusions: A very weak correlation exists between workers' compliance in using PPE and the potential impact of cyanide exposure in the HLO irrigation area of PT Bumi Suksesindo.